Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2019)
Dear Reader, We are pleased to introduce the second issue of the eleventh volume of the Law, State and Telecommunications Review (LSTR). In this issue, the journal published a number of original articles on topics relevant to ICT and telecommunications from a myriad of interdisciplinary perspectives. We are delighted to include articles on website promotion and protection of intellectual property in Spain, the European Audiovisual Commucation Directive and the regulation of the obligation of early financing of European works for the VOD segment, technologies of dynamic access and shared use of the radioelectric spectrum, application of the obligation to do as a regulatory saction in Brazil, geoblocking and geopricing in light of the public interest theory, concessionaries assets reversibility in local fixed telephony, DNS and ICANN, and planned obsolescence and consumer protection in Luso-Brazilian law. For future issues, we will continue to publish articles on all relevant areas of ICT and telecommunications. We hope you have enjoyed reading this issue looking forward to a twelveth volume to be released on May 2020. Sincerely, Prof. Marcio Iorio Aranha Editor-in-Chief, The Law, State and Telecommunications Review On behalf of the Editorial Board